ANALISIS KUALITATIF IMPLEMENTASI KEPDIRJENPENDIS NO. 1111 TAHUN 2019 TENTANG PETUNJUK TEKNIS PENILAIAN KINERJA KEPALA MADRASAH TSANAWIYAH NEGERI DI MASA PEMBELAJARAN DARING UNTUK PENGEMBANGAN MUTU MADARASAH - Deni Sunarya (JOEL: Journal of Educational and Language Research, 2021)
Qualitative Analysis of Implementation of Kepdirjenpendis No.IIII of 2019 concerning Technical Instructions for Performance Assessment to State Madrasah Tsanawiyah During the Online Learning Period for Efforts to Develop Madrasah Quality in Sukabumi Regency. The Head of Madrasah is one of the components of education that plays the most role in improving the quality of education as stated in Law Article 12 paragraph 1 PP 28 which states that "The Head of Madrasah is responsible for the implementation of educational activities, school administration, coaching other education personnel and the utilization and maintenance of infrastructure " This means that the madrasah principal must be able to become an educator, manager, administrator, supervisor, leader, innovator, motivator and entrepreneur in the school he leads in simple language, the madrasah principal must be able to manage his school well. This study aims to describe the Implementation Analysis of Kepdirjenpendis No.IIII 2019th teacher innovation on the performance of madrasa heads at the institutions they lead and analyze the efforts to develop the quality of madrasas used in improving the quality of education. The method in this, study uses a qualitative descriptive study and tries to be a mix method of the relationship between qualitative and quantitative. The selection of this method, will make it easier to understand the explanation of the data that has been explained because it is arranged accurately and systematically. The data collection of this research used the method of observation, interviews (interviews) and documentation. After that the data that has been collected is analyzed with the stages of data reduction, data presentation and the last is verification or drawing conclusions.